Leading with presence : fundamental tools and insights for impactful, engaging leadership - Knoppers, Antonie T.; Obdeijn, Milly; Giessner, Steffen R. (Emerald Publishing Limited, 2021)
In our communication, there are three 'elements' used to express a message: verbal content, body language, and the voice. When these elements are not congruent, we often will believe the body language and the voice. For this reason, non-verbal elements are particularly important for communicating feelings and attitudes and in engaging others; in any type of leadership role these aspects are vital in order to be an effective leader. 'Leading with Presence' provides a practical guide as to how and why Presence in everyday interaction is a vital component of impactful leadership. This book explores and teaches about non-verbal communication such as posture, gestures, and the voice to create more awareness and understanding of the signals sent, and explains how to be present and 'in the moment,' how to connect with others, to 'read the room,' to motivate and inspire, to instill trust, to exude confidence and thus strengthen your leadership. Through theory, practical tools and exercises, this book is essential reading for all business professionals in understanding the science behind body language, and exploring, practicing and understanding Leadership Presence.
Includes index.
Keywords: Leadership.; Nonverbal communication.; Communication in management.; Body language.; Business & Economics -- Leadership.; Management: leadership & motivation.; elektronické knihy; electronic books